Palmoplantar keratoderma climactericum successfully treated with topical oestrogen - T. E. Norman; O. Obed; A. Chen; S. D. Worswick (Wiley, 2024)
Abstract Keratoderma climactericum is characterized by palmoplantar hyperkeratosis developing after the onset of menopause. Although rare, keratoderma climactericum can profoundly impact quality of life and may be refractory to prescription‐strength topical steroids and keratolytics. We report a 52‐year‐old female with a 1‐year history of palmoplantar keratoderma. She had a medical history of generalized anxiety disorder and had reached menopause 2 years before presentation. Previously failed treatments included clotrimazole 1% cream twice daily, triamcinolone 0.1% cream twice daily, and betamethasone 0.05% cream mixed with tazarotene 0.1% cream twice daily. She was diagnosed with keratoderma climactericum, and conjugated oestrogen 0.625 mg/g cream twice daily was initiated. After 4 weeks, she had dramatically reduced erythema and hyperkeratosis of her bilateral palms and soles. No adverse effects to treatment were reported. Although the utility of topical oestrogen for keratoderma climactericum has been debated, our case provides further evidence for its efficacy and safety.